Temperature Monitoring System Based on PLC - Shoucheng Ding; Wenhui Li (Institute of Advanced Engineering and Science, 2013)
The programmable controller is an industrial control computer; it is the new automatic device inherited computer, automatic control technology and communication technology. System temperature signal detected by the temperature sensor. The temperature transmitter will be the temperature value converted into a voltage signal of 0-10V into PLC. PLC voltage signal setting compared to the temperature deviation after PID operation; the system will issue a temperature control signal to reach the electric heater voltage control. So that it implements a continuous control of the temperature. The temperature monitoring system in the industrial field has a certain value. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3988